Azo-Açiloksim ester başlatıcısı ile blok kopolimer sentezi - İmamoğlu, Tülin (Fen Bilimleri Enstitüsü, 1994)
İstenen fiziksel ve kimyasal özelliklere sahip polimerik malzeme sentezi yönünde yoğun araştırılmalar sürdürülmektedir. Bilinen geleneksel yöntemlerin yanısıra son yıllarda geliştirilen iki fonksiyonlu başlatıoılar yardımıyla da kimyasal yapıları farklı blok kopolimer sentezleri gerçekleştirilmiştir. Azo-açiloksim ester [A0E1 başlatıcıları ısısal ve fotokimyasal duyarlı iki ayrı işleve sahip serbest radikal başlatıoı larıdır. Bu çalışmada AOE başlatıaısı kullanılarak fotoaktif polimerler sentez edilmiştir. Bu polimerler aydınlatıl dıklarında, yapılarında bulunan azo-açiloksim ester' in parçalanmasıyla oluşan makroradikallerin etkisiyle, ikinci bir monomeri kullanarak, blok kopolimer sentezine olanak sağlarlar. Bu sentezlerde, monomer çifti olarak stiren ve metil metakrilat seçilmiştir. Blok kopoli- merizasyonun verimine, aydınlatma süresi, fotoaktif polimer konsantrasyonu ve molekül ağırlığı etkileri çalışılmıştır.

Production of new materials which have different porperties is the focus of the researches. Therefore, several kind of methods were tried in industry or in research laboratories to produce new materials. Block copolymer synthesis is the most succeful one among these methods to produce the materials needed in industrial applications. Block copolymers are used as additives e.g. surfactants and viscosity improvers. These polymeric features are avilable in "High Teah", and also Textile, Cosmetic Industries. The aim of this study is to synthesize block co polymer and increase the block copolymer yield. That is why, in this research an alternative procedure was investigated to synthesize block copolymers. The difference of the procedure is based on the usage of a multifunctional initiator. Azo-acyloxime ester (AOE) is the bifunctional initiator which is used to synthesise block copolymer in this procedure. AOE is synthesized by condensation of 4.4'-azobis (cyano pentonoio acid chloride) (APC) with 1- (A'-hydrox'yphenyl) -1,2- propanedione -2- oxirae (HPO). VI AOE bifunctional inititor has two functional groups which are able to produce free radicals. The free radical production phenomena depends on decomposition of photoactive and therraoactive groups. O CK, O CH, CH. r /-r\ ii i ii ' > Ll -i t^Pl-C-C =N-0-C-CH2-CHr C- N = N -C = CH-C^- C -J- The photoactive group I CN CN The thermoactive group [A0E1 AOE; initiator first step prepolyraer the second decomposed by adding Therefore, properties using the polymeriza the bifunctional initiator is an appropriate for two-step polymerization process. In the, the "thermoactive group" is decompozed and a is synthesized by addition of a monomer. In step, "the photoactive group" in prepolymer is by irradiation and block copolymer synthesized a different kind of monomer to the system, a block copolymer which posseses different of its own monomers could be synthesized by se two different monomers in a two step tion process. In a s imi liar way, styrene (St) and methyl metacry- late (MMA) monomers couple was used in this procedure. The two-step synthesis process of St-MMA copolymer proceeds shown at Scheme 1. VII OCK O II ı 3 CH, I /7^\ H I II I " "tO-^J^-oc =n-0-C-CH2-CH2- C- N = N _ CH O II ~1 CN neat C = CH-CH -C-I- I 2 2 3n CN \k CH. O CH O -°-\L)/-C-C =N- O- C-CH2- CH - C. CN styrene Ni/ CH, OCH3 ° "°~V^7 C~c =N-°-c-CH2-CH -C -CH2-ÇH CN hV.Ni/ CH3 0"^)~C, + CH3CN+C02+*CH2~CH2-9-CH9-£H methyl.metacrylate PS t - "b - PMMA CN CO] methyl metacrylate P3t - ü -PMMA Scheme 1. Synthesis of St MMA. block copolymer "by using AOE initiator. VIII The first step of the synthesis of St-MMA block copolymer is the pol imerization of styrene by using AOE initiator. Different concentrations of AOE initiator was prepared by dissolving in tetrahydrofuran (THF). Then, different volumes of styrene monomer were added to the solutions of AOE initiator. During this preparations nitrogen gas passed through the system. Finally, the solutions which were prepared in schlenk tubes and degassed by nitrogen gas placed in water bath to initiate thermal decomposition. The resulting polimeria mixtures were precipitated in methanol. The results of the synthesis of polystyrene is given in Table 1. Table 1. Synthesis of polystyrene by using AOE initiator. AOE mole/1 Duration (Min)* Conversion Mn 7.01x10 -3 180 4.24x10 3.52x10 -3 180 12 2.06x10' 3.52x10 -3 120 9.39x10 * Thermal decomposition was proceed at 60 °C St : 16 mL THF 2 mL According to the Table 1, the concentration of initiator and the duration of thermal decomposition affects the degree of conversion and molecular weight of polystrene. IX The second step of the synthesis of St-MMA block copolymer, is photoctive decomposition of polystyrene which has photoactive groups in its structure. Due to synthesise St-MMA block copolymer, different concen trations of polystyrene was dissolved in THF solvent and then, different volumes of methyl metacrylate monomer were added to the solutions. During the preparation of the solutions, nitrogen gas was passed through the system. Later, the final solution was irradiated with a 350 nra U.V. lamb. The product; St-MMA block copolymer was precipated in methanol. Block copolymer mixture which also include homopolystyrene and homopolymethyl metacrylate was. separated and dried. Homopolystyrene and homopolymethyl metacrylate were extracted with c-hexane and aaetonitrile solvents respectively. The effect of irradition time, concentration and molecular weight of polystyrene on the synthesis of block copolymer was studied. In the Table 2, the synthesis of St-MMA block copolymer is given. Table 2 : Synthesis of St-MMA block copolymer, *[MMA1 = 6.27 mole/1 Table 2 enables us to study the several effect on the blook copolymer synthesis. As the percentage of molecular weight of prepolystyrene increases the percantage of block copolymer raises. In the same manner as the concentration of polystyrene increases the percentage of blook copolymers also increases. Besides this, there is a definite relationship between irradiation time and block copolymer percentage. As a result, by using bifunctional AOE initiator St-MMA block copolymer was synthesized in a two step mechanism. St-MMA block copolymer has physical properties of each of the.styrene and methyl metacrylate monomers. This special property makes the blook copolymer available in industry.
Synthesis of block copolymer by azo-acyloxime ester initiator
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1994
Keywords: Kimya; Azo-açiloksim; Esterler; Kopolimerler; Chemistry; Azo-acyloxime; Esters; Copolymers